2008
DOI: 10.1007/s10164-008-0136-6
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and laterality of hand use in free-ranging aye-ayes (Daubentonia madagascariensis) and a comparison with captive studies

Abstract: We observed hand use in free-ranging aye-ayes (Daubentonia madagascariensis) on an island in the Mananara River, eastern Madagascar. The results were compared with those of two conflicting studies on hand laterality in captive aye-ayes. We argue that patterns of hand preference in wild aye-ayes are comparable to those of captive animals and that discrepancies between studies are-at least partly-caused by different ways of collecting and processing data. Aye-ayes fit Level 2 of the categories of hand laterality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 33 publications
1
9
1
Order By: Relevance
“…However, in some primate species sex affects only the strength of limb preferences [91,92], and in many others no differences in preferential hand use between males and females was found at all [54-60]. At the same time, non-primate quadrupeds seem to display more pronounced and contrasting sex differences in manual laterality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some primate species sex affects only the strength of limb preferences [91,92], and in many others no differences in preferential hand use between males and females was found at all [54-60]. At the same time, non-primate quadrupeds seem to display more pronounced and contrasting sex differences in manual laterality.…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences in motor preferences have been described in many primates (e.g., [46-51]). Generally, bias for use the left hand is more characteristic of males, whereas a greater right-hand use has been noted for females (e.g., [8,48,50,52,53]); although a number of primate studies failed to reveal any differences in motor laterality between the sexes [54-60]. The most pronounced sex differences in manual laterality have been reported for non-primate quadrupedal mammals.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous literature on lemur manual lateralization, the finding of a group‐level hand preference is quite unusual. Indeed, prior studies on this topic usually failed to reveal a significant bias in hand use for simple reaching and other unimanual actions [Leliveld et al, ; Lhota et al, ; Rigamonti et al, ; Schnoell et al, ], although it has been reported a tendency toward a left‐handedness in strepsirrhines [for review, see: Ward et al, ], including a sample of ring‐tailed lemurs [Milliken et al, ; Shaw et al, ]. However, as mentioned above, most studies on strepsirrhine hand preference have relied on the measurement of simple and spontaneous actions.…”
Section: Discussionmentioning
confidence: 99%
“…[for review, see Ward et al, ] and Senegal bushbabies ( Galago senegalensis ) [Larson et al, ; Sanford et al, ]. More recently, it has been reported a lack of group‐level hand preference in Malagasy strepsirrhines for foraging and other spontaneous natural activities in species such as indri ( Indri indri ) [Rigamonti et al, ], M. murinus and M. lehilahytsara [Leliveld et al, ], aye‐ayes ( Daubentonia madagascariensis ) [Lhota et al, ], and red‐fronted lemurs ( Eulemur rufifrons ) [Schnoell et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Such digital morphology functions to facilitate percussive foraging or tapscanning (Erickson 1991(Erickson , 1995(Erickson , 1998Erickson et al 1998), a haptic-auditory behavior that contributes to the detection of embedded beetle larvae and to the material assessment of foods (Ancrenaz et al 1994;Andriamasimanana 1994;Iwano 1991;Iwano and Iwakawa 1988;Lhota et al 2008Lhota et al , 2009Petter and Peyrieras 1970;Pollock et al 1985;Sterling 1994;Sterling and McCreless 2006;Sterling et al 1994). Accordingly, aye-ayes are described as having a well-developed sensorimotor intelligence (Gibson 1986;Sterling and Povinelli 1999) that is supported in part by a large and expanded somatosensory cortex (Kaufman et al 2005).…”
Section: Aye-ayesmentioning
confidence: 95%